Rectal Mucinous Adenocarcinoma Invading Retrorectal Dermoid Cysts: A Case Report - Wang, Rui; Yan, Zhaopeng (Frontiers in Oncology, 2019)
Rectal mucinous adenocarcinoma is a subtype of colorectal adenocarcinoma, which is more aggressive and prone to invade adjacent normal organs or tissues compared with non-mucinous adenocarcinoma. Retrorectal dermoid cyst is a rare congenital disease, which usually are benign but with a potential for malignant degeneration. In this article, we report a case which presented a rectal mucinous adenocarcinoma invading into retrorectal dermoid cysts, indicating that besides adjacent normal organs or tissues, malignancies can also invade adjacent tumors, making their diagnosis and management more complicated. In such cases, double primary tumors should be considered, and they should be removed surgically.